DOMESTIC VIOLENCE STUDY IN A SAMPLE OF LATINO WOMEN LIVING IN THE UNITED STATES - Zarza González, María José; Froján Parga, María Xesús (Anales de Psicología / Annals of Psychology, 2005)
This article focus on the study of domestic violence within a sample of heterosexual Latino women (N=46) married for at least 6 months. The study includes: Demographic factors; attitudes toward women; violence against their male partners and children; and a history of violence and family instability in subjects’ childhood. Results show a pattern of interactive violence between both male and female partners as well as an association between both parents’ violence against their children, in what seems to be in males a learnt behavior from childhood. In addition, this study stresses the need of further psychological studies on domestic and family violence to complement the predominant sociological theories.